Poloxamer 407-induced atherosclerosis in mice appears to be due to lipid derangements and not due to its direct effects on endothelial cells and macrophages - Thomas P. Johnston; Yuai Li; Ahmed S. Jamal; Daniel J. Stechschulte; Kottarappat N. Dileepan (Mediators of Inflammation)
Coronary heart disease secondary to atherosclerosis is still the leading cause of death in the US. Animal models used for elucidating the pathogenesis of this disease primarily involve rabbits and pigs. Previous studies from this laboratory have demonstrated intraperitoneal injections of poloxamer 407 (P-407) in both male and female mice will lead to hyperlipidemia and atherosclerosis, suggesting the use of this polymer to develop a mouse model of atherosclerosis. In order to understand the mechanism of P-407-induced hyperlipidemia and vascular lesion formation, we evaluated the direct effects of P-407 on endothelial cell and macrophage functions in vitro, and its in vivo effects on the oxidation of circulating lipids following long-term (4 month) administration. Our results demonstrated that incubation of P-407 with human umbilical vein endothelial cells in culture did not influence either cell proliferation or interleukin-6 and interleukin-8 production over a concentration range of 0-40 μM. In addition, nitric oxide production by macrophages was not affected by P-407 over a concentration range of 0-20 μM. Finally, we demonstrated that while P-407 could not induce the oxidation of LDL-C in vitro, long-term (4 month) administration of P-407 in mice resulted in elevated levels of oxidized lipids in the plasma. Thus, it is suggested that the formation of atherosclerotic lesions in this mouse model of atherosclerosis does not result from either direct stimulation of endothelial cells or macrophage activation by P-407. Instead, these data would support the premise that oxidation of lipids (perhaps low-density lipoprotein cholesterol) by an indirect mechanism following injection of P-407 may represent one of the mechanisms responsible for atheroma formation.